Acinar Melanosis of the Bartholin Gland: A Report of 3 Cases. (January 2022) - Khera, Kaveri M.; Moghimi, Ali; Cataldo, Leigh; Kumar, Beena; Gibbs, Paul M.
Abstract : Melanocytic pigmentation occurs in multiple sites in the lower female genital tract, but is rare within benign cysts of the vulva. We report 3 patients with multiloculated cystic lesions of the vulvar vestibule exhibiting prominent melanocytic pigmentation. The current cases differ from a previous report of melanosis in a Bartholin gland cyst in that the population of melanocytes occupies the acinar structures of the gland, rather than a squamous-lined surface. A similar cell population is demonstrated by immunoperoxidase methods in a fourth patient's nonpigmented gland, suggesting that melanin production may arise in a native, rather than metaplastic, cell population.